Challenges in Primary Hip Arthroplasty for Neglected Post‑traumatic Hip Dislocations with Acetabular D: Acetabular defect - Maitama, Mohammed Inuwa; Lawal, Yau Zakari; Ejagwulu, Friday Samuel; Kabir, Abubakar Mohammed; Ismaila, Lawal Dahiru (Nigerian Journal of Orthopaedics and Trauma, 2020)
Primary hip arthroplasty in the presence of acetabular defect seen in patients with neglected post‑traumatic hip dislocation is quite challenging due to the need in securing stability of hemispherical cup and providing enough rigid fixation needed to prevent acetabular cup micromotion. In segmental acetabular defect, contained or uncontained, there is an acetabular rim violation, an important risk factor for cup micromotion, loosening in the long term and subsequent failure. In our environment, most of the patients with post‑traumatic hip dislocation present late, making conservative management (closed reduction and traction) or primary acetabular restorative reconstruction very difficult, hence the surgeon is left with the option of either Girdlestone excision arthroplasty, arthrodesis, hemiarthroplasty or total hip replacement. For the few who present early, most of them may not afford the cost of surgery (total hip replacement) and majority of centres in developing countries do not have facilities and trained personnel to handle such complex procedures. Impaction of cancellous bone graft to the acetabular defect is a common practice among arthroplasty surgeons. This, however, does not guarantee bony ingrowth at cup/graft interface and initial rigid fixation. The resultant acetabular cup micromotion on commencing weight‑bearing would affect biologic fixation and may explain the relatively high incidence of loosening in this category. It is with this background that we review this important topic in hip arthroplasty highlighting various options of treatments, outcomes and recommendations.